Studi Kasus Pelayanan Rekam Medis pada Masa Pandemi Covid-19 Di Puskesmas Gondokusuman II Kota Yogyakarta - Angga Eko Pramono; Marko Ferdian Salim; Anita Wijayanti (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda, 2022)
The Covid-19 outbreak has been declared as a public health emergency of international concern by the World Health Organization (WHO). The pandemic has also changed the process of health services provided to patients, including medical record services. This study aimed to examine the process of medical record services at the Gondokusuman II Primary Health Center (PHC) in Yogyakarta City during the Covid-19 pandemic. This qualitative research explored medical record services during pandemics. Three staff were recruited as respondents using the purposive sampling technique. Data were collected through observation and interviews. There were differences in patient registration services before and after the pandemic. Before registering, patients will be screened first. If they show Covid-19 symptoms, the patients are directed to the infectious clinic and the provision of medical records will be prioritized. To support the implementation of health protocols, the primary health center provides personnel protective equipment adequately. However, the reference for health protocols related to medical record services at the PHC level is not yet available. So, reference issued by the Ministry of Health is used respectively. Therefore, specific regulations need to be immediately compiled and disseminated to ensure that the prevention of Covid-19 transmission can be carried out more precisely.